Reduction of uncertainty using adaptive modeling under stochastic criteria of information content - Garanin, Dmitry Anatolyevich; Lukashevich, Nikita Sergeevich; Efimenko, Sergey Vladimirovich; Chernorutsky, Igor Georgievich; Barykin, Sergey Evgenievich; Kazaryan, Ruben; Buniak, Vasilii; Parfenov, Alexander (Frontiers in Applied Mathematics and Statistics, 2023)
Entropy is the concepts from the science of information must be used in this situation where un-defined behaviors of the parameters are unknown. The behavior of the casual parameters representing the processes under investigation is a problem that the essay explores from many angles. The provided uniformity criterion, which was developed utilizing the maximum entropy of the metric, has high efficiency and straightforward implementation in manual computation, computer software and hardware, and a variety of similarity, recognition, and classification indicators. The tools required to automate the decision-making process in real-world applications, such as the automatic classification of acoustic events or the fault-detection via vibroacoustic methods, are provided by statistical decision theory to the noise and vibration engineer. Other statistical analysis issues can also be resolved using the provided uniformity criterion